PENGEMBANGAN JOB SHEET CLEANING BATHROOM SEBAGAI ROOM ATTENDANT PADA HOUSEKEEPING DEPARTMENT - Siti Indah Nurhamiddiyanti, - (2020)
This research in the background by conditions of the availability of job sheet in the smk Negeri 9 Bandung not referring to the components job sheet that should be and job sheet, not appropriate SOP hotel. This research aims to (1) plan to the development of the job sheet cleaning bathroom according to the needs. (2) producing job sheets in development according to the components of the job sheet based on the analysis of the needs of. (3) evaluate with conduct validity job sheet cleaning bathroom. Through expert judgment this research using the model PPE ( planning, production, and evaluation). The results of research suggest that : (1) planning based on the needs of planning development job sheet cleaning bathrooms because job sheet available not referring to the components job sheet and still be handbook teachers and not appropriate SOP. (2) production job sheet in the preparation covering the practice of the safety of work, grooming. The implementation of the job sheet to the practice of splits into 4 activities. The results of the assignment adapted to match every job sheet and directive self-evaluation. (3) Researchers do validation (Expert judgment) job sheet to 4 validation which 2 experts curriculum and, 2 experts the matter to assess the feasibility of job sheet cleaning bathroom that had been in development, the validation by the curriculum and the material job sheet cleaning bathroom was valid to obtain the average 94,75 % including criteria very worth without revision. For researchers can continue this research implementation job sheet cleaning bathroom attendant this housekeeping department to learners SMK Akomodasi Perhotelan.